Utilization of the Internet of Things in Creating Smart Room Customization and Improving the Quality of Services in the Tourism and Hospitality Industry - Septa Intiar; Arief Nuryana; M.Syahputra; Rahmawati; A., Amiruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study is a qualitative study with a descriptive approach, namely describing each main object used in this study, including the Internet of Things, Smart Room Customization, and Service Quality. The data used in this study are secondary data that researchers obtain from various credible sources such as books, scientific articles, credible websites, and various other research sources. The data obtained are analyzed by stages of data collection, data reduction, and drawing conclusions. The result in this aticle show. the Internet of Things can create smart Room Customization. Smart Room Customization is built using the concept of the Internet of Things (IoT), a concept where an object has the ability to receive and send data over a network without requiring human interaction to a computer. The Internet of Things (IoT) is a concept that aims to expand the benefits of continuously connected internet connectivity. Kaur, Singh, Khairwal, & Jain conducted a study on the Home Automation and Security System with the GSM communication method and Android Application, the system can control equipment and help protect thieves because there is an alarm and can send signals to the owner using Android [. Giorgos Sfikas also conducted a study Creating a Smart Room using an IoT approach, a study that explains the concept of building a Smart Room using Arduino and a Bluetooth module to control electronic equipment. In the end, the benefits that the researcher mentioned above serve to facilitate customers in accessing, utilizing facilities, and other things that can facilitate customers to travel and stay in an integrated place and hotel. The convenience that the researcher mentioned above is one form of improving the quality of tourism services.